The The use of rice husk ash, saw dust and coconut fiber (CASE2SK) in a diesel engine at sawmill industry - Safira Kusuma; Heru Subaris Kasjono; Yamtana (Poltekkes Kemenkes Yogyakarta, 2022)
The machine has noise with a high-power sound, one of the negative impacts it causes is Noise Induced Hearing Loss (NIHL), for this reason it needs a material that can reduce noise. The result of the measurement of the noise level at this sawmill industry is 96.95 dBA which exceeds the TLV, according to Permenkes No. 70 of 2016 concerning Standards and Health Requirements for the Industrial Work Environment, which is 85 dBA. The purpose of this study was to determine the effect of using a mixture of rice husk ash, sawdust and coconut fiber in a diesel engine to reduce the noise level in the sawmill industry. This type of research is a True Experiment with a pretest – posttest design with a control group, with the object of the research being a diesel engine that will be repeated 16 times at one point for each group, namely the control and experimental groups. The average reduction in bulkhead noise level is 13.08 dBA or 14.03%, with the noise level after treatment is 80.14 dBA. The Wilcoxon test to test the pre data with the control group post and the pre data with the post experimental group, the value of p = 0.000 which means less than 0.05, it can be concluded there is a difference between the noise level. Pretest and posttest in the control and experimental groups, and the independent t test obtained p value = 0.000 it means that there is a significant difference between the control group and the experimental group. However, the percentage of reduction was higher in the experimental group, so it is still advisable to use a mixture of rice husk ash, sawdust and coconut husk.